6x-7y+9=0

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Move all terms not containing y to the right side of the equation.

Subtract 6x from both sides of the equation.

-7y+9=-6x

Subtract 9 from both sides of the equation.

-7y=-6x-9

-7y=-6x-9

Divide each term by -7 and simplify.

Divide each term in -7y=-6x-9 by -7.

-7y-7=-6x-7+-9-7

Cancel the common factor of -7.

Cancel the common factor.

-7y-7=-6x-7+-9-7

Divide y by 1.

y=-6x-7+-9-7

y=-6x-7+-9-7

Simplify each term.

Dividing two negative values results in a positive value.

y=(6)x7+-9-7

Dividing two negative values results in a positive value.

y=6×7+97

y=6×7+97

y=6×7+97

Rewrite in slope-intercept form.

y=67x+97

y=67x+97

Rewrite in Slope-Intercept Form 6x-7y+9=0